2012
DOI: 10.1098/rstb.2012.0006
|View full text |Cite
|
Sign up to set email alerts
|

Judgements of agency in schizophrenia: an impairment in autonoetic metacognition

Abstract: We investigated judgements of agency in participants with schizophrenia and healthy controls. Participants engaged in a computer game in which they attempted to touch downward falling Xs and avoid touching Os. On some trials, participants were objectively in perfect control. On other trials, they were objectively not in complete control because the movement of the cursor on the screen was distorted with respect to the position of the mouse by random noise (turbulence), or it was lagged by 250 or 500 ms. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 55 publications
2
61
1
1
Order By: Relevance
“…This finding bolsters previous evidence for the notion that metacognitive skill in one domain may not necessarily translate to another (David et al, 2012;Metcalfe et al, 2012;Pannu & Kaszniak, 2005;Schnyer et al, 2004). Furthermore, our results indicate that metacognitive accuracy in each domain was related to regional differences of white matter microstructure.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding bolsters previous evidence for the notion that metacognitive skill in one domain may not necessarily translate to another (David et al, 2012;Metcalfe et al, 2012;Pannu & Kaszniak, 2005;Schnyer et al, 2004). Furthermore, our results indicate that metacognitive accuracy in each domain was related to regional differences of white matter microstructure.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, schizophrenic patients appear to have a relatively preserved capacity to make retrospective metacognitive judgments of their memory as well as trialby-trial judgments of their performance accuracy, despite showing significant impairment in metacognitive judgments of their own agency as well as a generalized impairment in insight into their disorder (David, Bedford, Wiffen, & Gilleen, 2012;Metcalfe, Van Snellenberg, DeRosse, Balsam, & Malhotra, 2012). Furthermore, preliminary studies in healthy individuals have suggested that there may be domain specificity in the neural basis of metacognitive ability in distinct cognitive domains.…”
Section: Introductionmentioning
confidence: 99%
“…A last measure of participant classification, entropy, was calculated on the basis of each model's posterior probabilities for group membership; values range from 0 to 1 with greater values reflecting superior classification of participants (Ramaswamy, Desarbo, Reibstein, & Robinson, 1993). The LPA was performed using MPLUS v. 7.3 (Muthén & Muthén, 1998-2012.…”
Section: Analysesmentioning
confidence: 99%
“…This perception, referred to as the sense of agency, is impaired in a very salient manner in a number of clinical conditions including schizophrenia (Metcalfe, Van Snellenberg, DeRosse, Balsam, & Malhotra, 2012) and the dissociative disorders (Spiegel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, severe mental illness could result in considerable impairments in everyday functioning [5][6][7], and from a cognitive perspective, research has found that patients with schizophrenia have a reduced metacognitive capacity [8] as well as difficulties with metacognitive agency [9].…”
Section: Autonomy and Severe Mental Illness: The Relationship Betweenmentioning
confidence: 99%